النسخ يف القرآن الكرمي ورد الشبهات عليه دراسة حتليلية - الملا, عبد الله صباح (Pusat Kelestarian Turath Islami, Fakulti Pengajian Islam, Universiti Kebangsaan Malaysia, 2018)
There were many works are recorded in the Qur'an studies. The scholars have focused on the history of the Qur'an revelation, Makkiyyah and Madaniyyah, the beginning and ending sentences of the Qur'an, reason of Qur'an's verses revelation, compilation of Qur'an and writing, nasikh and mansukh, mujmal and mubayyan, stories, oaths, and exegesis. Hence, the debates on the studies became wider. The scholars have deepened this field and issued precious gems from it. Through the debate of the knowledge of nasikh and mansukh in this important Qur'an, the researcher also contributes to rejection of the disbelievers through their disputes, among the non-Muslims. Similarly, rejection also done to the same kind religion in Muslims either from the past or present group.